Study of Body Composition, Lung Function, and Quality of Life Following Use of Anabolic Steroids in Patients With Chronic Obstructive Pulmonary Disease. (April 2014) - Daga, Mradul Kumar; Khan, Naushad Ahmad; Malhotra, Varun; Kumar, Suman; Mawari, Govind; Hira, Harmanjit Singh
Background : Chronic obstructive pulmonary disease (COPD) is characterized by irreversible airflow limitation and is associated with weight loss and decreased muscle strength and exercise capacity. Methods : A double-blinded randomized controlled trial of 32 male COPD patients (age, 54.94 ± 11.27 years) was carried out to assess effects of anabolic steroid in terms of a daily high-protein, high-calorie diet alone or one combined with anabolic steroids on body composition, lung function, and health-related quality of life (HRQL). Outcomes were assessed by anthropometric and spirometric measurements, peak expiratory flow rate, partial pressure of oxygen in arterial blood, 6-minute walk test (6MWT), hand grip test, and HRQL index scores. Measurements were made at baseline and end of treatment (6 weeks). Results : All patients showed significant difference ( P < .001) in pulmonary function parameters and anthropometric measurements after 6 weeks of intervention (within-group changes); however, no significant improvement occurred in the pulmonary function parameters between the groups. The difference in exercise capacity (6MWT) and HRQL scores in the treatment group were statistically significant ( P < .001) compared with control group after 6 weeks of intervention. In the treatment group, the average 6MWT distance increased from 213.5 m to 268.5 m at 6-week follow-up, and HRQL scores increased from 101.25 to 118.45. Also, HRQL and 6MWT parameters were positively correlated in response to steroid supplementation at the end of the study. Conclusion : Weekly administration of anabolic steroids during 6 weeks increased exercise capacity and quality of life in patients with COPD.